2020
DOI: 10.1039/c9nj04408f
|View full text |Cite
|
Sign up to set email alerts
|

Study of the complexation of structurally modified curcumin with hydroxypropyl beta cyclodextrin and its effect on anticancer activity

Abstract: This study aims at modifying curcumin to curcumin pyrazole and complexing it with HPβCD employing a simple protocol to improve curcumin's chemical–physical properties and biological activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 40 publications
4
21
0
Order By: Relevance
“…In vitro cytotoxicity study is commonly employed to evaluate the potential of samples to induce cell death. 39 The results displayed in Fig. 8 showed that the in vitro cytotoxicity of samples was improved with the increase of sample concentration.…”
Section: In Vitro Cytotoxicity Studymentioning
confidence: 93%
“…In vitro cytotoxicity study is commonly employed to evaluate the potential of samples to induce cell death. 39 The results displayed in Fig. 8 showed that the in vitro cytotoxicity of samples was improved with the increase of sample concentration.…”
Section: In Vitro Cytotoxicity Studymentioning
confidence: 93%
“…Large irregular particles of commercial nimodipine (Nim) are depictable in Figure 5 [ 29 ], while spherical shells with circular holes of hydroxypropyl-β-cyclodextrin, (Hp-β-CD), with a particle ranging from 25 to 100 μm, are shown in Figure 5 [ 30 ]. For methyl-β-cyclodextrin, Me-β-CD, fragments of spherical shells are presented in Figure 5 [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…In both physical mixtures, curcumin peak was broadened and shifted to slightly lower wavelength (3441 cm −1 ) suggestive of slight hydrogen bond formation. However, in the spectra of the improved SD/P4 and 6, the complete absence of curcumin peak along with other identifying peaks in the 1700–1500 cm −1 region, along with the shift of HPβCD peaks to lower wavelength (3398 cm −1 ), might indicate possible formation of inclusion complex, 80 , 81 possibly through hydrogen bond formation with –OH of curcumin.
Figure 4 FT-IR spectra of ( A ) curcumin, ( B ) lecithin, ( C ) cholesterol, ( D ) SA, ( E ) PLX 188, ( F ) HPβCYD, ( G ) SD/P4 improved physical mixture, ( H ) SD/P6 improved physical mixture, ( I ) improved SD/P4 formulation and ( J ) improved SD/P6 formulation.
…”
Section: Fourier Transform Infrared Spectroscopy (Ft-ir)mentioning
confidence: 96%
“…Again, we can notice the absence of curcumin peak, which when considered together with the shift and intensive broadening of HPβCD peak, further indicate the possible formation of inclusion complex. 80 , 81 …”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
See 1 more Smart Citation